The Effect of Price, Promotion and E-Service Through The McDonald's Application On Consumer Buying Interest - Ridvandani Thalib, Rizqy; Machmud , Rizan; Amir Isa, Ramlan (International Journal of Multidisciplinary Applied and Science Research, 2025)
The development of digital technology has changed consumer behavior, including in terms of purchasing fast food. The McDonald's application as one of the digital ordering facilities offers easy access, attractive promotions, and technology-based services (e-service). This study aims to analyze the effect of price, promotion, and e-service through the McDonald's application on consumer purchasing interest. The research method uses a quantitative approach by distributing questionnaires to 96 respondents who use the McDonald's application in Indonesia. Data were analyzed using multiple linear regression analysis with the help of SPSS software. The results of the study indicate that price does not affect consumer purchasing interest, promotion has a positive effect on consumer purchasing interest, e-service has a positive effect on consumer purchasing interest, and simultaneously the price variable, promotion, with the promotion variable as the most dominant factor. These findings provide practical implications for the management of McDonald's Gorontalo and similar business actors in improving digital marketing strategies to encourage consumer purchasing interest.